Comparative efficacy and safety of febuxostat and allopurinol in chronic kidney disease stage 3–5 patients with asymptomatic hyperuricemia: a network meta-analysis - Jiaojiao Chen; Yanyun Zhang; Yinglin Wang; Lu Chen (Renal Failure)
Objective This study evaluates and compares the effectiveness and safety of febuxostat and allopurinol in chronic kidney disease (CKD) stages 3–5 patients with asymptomatic hyperuricemia using a network meta-analysis.Methods A systematic review and network meta-analysis were conducted, adhering to PRISMA-NMA guidelines. Searches included PubMed, Embase, Cochrane Library, and Chinese databases up to June 2024. Randomized controlled trials (RCTs) and cohort studies were assessed for methodological rigor using GRADE.Results A total of 12 RCTs and 4 cohort studies (n = 2,423 participants) were included. Febuxostat was associated with greater improvements in estimated glomerular filtration rate compared to allopurinol (MD, 4.99 mL/min/1.73 m2; 95%CI −0.65 to 10.78; certainty: low) and placebo (MD, 4.72 mL/min/1.73 m2; 95%CI 0.67 to 8.82; low). Serum uric acid reduction was also more pronounced with febuxostat (MD, −0.61 mg/dL; 95%CI −1.15 to −0.05; moderate). Safety outcomes, including major cardiovascular events and adverse events, showed no significant differences between febuxostat and allopurinol. Subgroup analyses revealed enhanced effectiveness of febuxostat at six months of treatment.Conclusions This analysis provides robust evidence that febuxostat might offers greater improvements in kidney function and uric acid levels compared to allopurinol or placebo in asymptomatic hyperuricemia with CKD stage 3–5 patients, without compromising safety. These findings can guide clinical decision-making and treatment optimization.